A hegemonia do capital na rede de governança do Fundo de Financiamento Estudantil (Fies) - Santos, Aline Veiga dos (2017)
This study has as object of research the Student Financing Fund (Fies), which is an educational policy with broad social dimension that aimed to promote the democratization of access and permanence in higher education by benefiting economically disadvantaged students. However, after its redesign in 2010, has developed as a marketing policy, which promotes the privatization and financialization of higher education, and consolidates the conglomerates. The investigation of the governance network of the Fies is embedded in a complex network of articulation and power between State (political society), and entrepreneurs of education (private hegemony apparatus). Given this scenario, demarcated by several actors that constitute the Expanded State, this study opted to place a magnifying glass over the node of Kroton network. Thus, the general objective was to investigate the contradictions generated by the correlation of forces between the State and private apparatus in the Fies governance network and Kroton articulations within this arena to maintain its hegemony as the largest conglomerate of higher education in the world. This is a critical-descriptive documentary research, based on Theory of Extended State and the Method of Analysis of Social Networks, using the technique of documentary analysis. The approach used was qualitative and quantitative. Regarding the treatment of documentary sources, the qualitative data were analyzed according to Critical Discourse Analysis, and the quantitative and financial data were analyzed in the light of Descriptive Statistics. In view of the extensive collection of information collected, it was used a resource to visualize the Fies governance network and weave the speeches of the Chamber and the Federal Senate. Gephi - free software - was used to graphically signal this network of relationships. Alceste - paid software, version 4.8/2012 - was used to analyze the speeches of the politicians and the networks actors invited to participate in the public hearings that debated the Fies. It was found that Kroton, from its modus operandi and the articulations of its representatives, became the largest beneficiary of Fies, followed by other educational companies. To a large extent, the exorbitant profit margins are closely related to the high number of students beneficiaries of Fies, since a significant portion of revenues derived from the payment of fees is guaranteed. In just three years, 2014, 2015 and 2016, the federal government transferred over R$ 6.8 billion to the institution. Kroton's Board of Directors is composed of former minister, former secretary of education, former federal deputy, former vice governor, and presidents and directors of main representative associations of the educational sector (ABMES, ANUP, CRUB, FERESP, SEMESP). Kroton, through its organic intellectuals, seeks to maintain a close relationship with the politicians that represent education entrepreneurs in the National Congress. The intention is to form networks of cooperation to preserve its hegemony over the whole of society. Therefore, its allies employ strategies to reach consensus, seeking the support of the population and the politicians to their political, economic and ideological project. Fies has been corroborating with the formation of oligopolies by passing on a large amount of resources to the institutions private-market. Fies is an extremely complex policy, which printed contradictory interests to their social character to maintain the hegemony of the private-sector market and give impetus to the financialization of education.